On the feasibility of monopile foundations for offshore wind in the Baltic Sea - van der Stap, Florian L. (author); Nielsen, Martin B. (author); Owen, C.C. (author); van der Male, P. (author); Hendrikse, H. (author) (POAC, 2023)
For the design of offshore foundations in regions such as the Baltic Sea, it is paramount that ice-structure interaction is appropriately considered. For the monopile, a common foundation for offshore wind turbines, challenges with ice-induced vibrations and high ridge loads may require ice-mitigating measures to be included in the design. A ‘feasibility map’ showing the necessity for such ice-mitigating measures in the entire Baltic region has been developed for monopiles. The feasibility was considered in technical terms by imposing design, installation, and fabrication constraints, and in economic terms, expressed in weight increase of monopiles when compared to an ‘ice-free’ design. A design assessment of offshore wind turbines across the Baltic Sea was conducted by optimizing foundation designs for the IEA 15 MW reference turbine for nine identified characteristic regions of the Baltic Sea. The assessment was performed via the in-house foundation design software MORPHEUS by Wood Thilsted. MORPHEUS has been coupled to the phenomenological ice model “VANILLA” to capture the dynamic ice-structure interaction for level ice. From the assessment, the following regions are deemed feasible for monopiles without ice-mitigating measures: the Danish Straits, the Baltic Proper South, the Baltic Proper North, the Gulf of Riga and the Archipelago Sea. The Bothnian Sea North and the Bay of Bothnia are deemed infeasible without mitigating measures. For the Bothnian Sea South and the Gulf of Finland, no conclusive answer was found as more research into the cost competitiveness of alternative options is required. The increase in fatigue resulting from ice loading was found to be the main cause for foundation weight increase of monopiles compared to monopiles designed for ice-free waters. Offshore Engineering